El desenredo del enredo (2020)
My project arises from the need to reconnect with my identity, but in a particular way. Although it does not really come from a disease, nor a syndrome or suffering, it comes from the consciousness of life and the short time it lasts. Life is to experience. In my project I play to be someone else without leaving to be myself. Play as characters for social networks, specifically Instagram and TikTok. This project was born from a confinement of reality, where I stopped being me, I disconnected, but I remembered that throughout my career I have worked with myself through art; In other words, this project consists of the emergence of three heteronyms, Margarita Walton, Fazio Dante and Olvido Mars. The final presentation of the characters is made through a web page, specifically designed for this purpose, seeking that the characters themselves let us know them.